PERAN MUSYRIF DALAM MEMBENTUK KARAKTER DISIPLIN SANTRI PONDOK PESANTREN IBNUL QAYYIM PUTRA TEGALYOSO PIYUNGAN BANTUL YOGYAKARTA - Rubini; M. Rifa’i (Elsalima (Salam Institute), 2024)
This study aims to determine the role of musyrif in shaping the disciplinary character of students at Ibnul Qoyyim Putra Tegalyoso Piyungan Islamic Boarding School Yogyakarta as well as the supporting and inhibiting factors.Data were obtained using documentation, interviews, and observation methods, while the subjects of this study were five musyrifs of Ibnul Qoyyim Putra Islamic Boarding School in Yogyakarta. Data analysis using the Miles and Huberman model begins with data reduction, data presentation, and data analysis in the form of descriptions. Ended with drawing conclusions/verification between theory and practice that occurs in the field.The results showed that the role of musyrif in shaping the disciplinary character of the students of Ibnul Qoyyim Putra Tegalyoso Piyungan Bantul Yogyakarta Islamic Boarding School is as a director, facilitator, informator, motivator, initiator. Supporting factors in the formation of the disciplinary character of students of Ibnul Qoyyim Putra Islamic Boarding School are the tole model of a musyrif, the implementation of active activities, as well as communication and assistance to students. inhibiting factors in the formation of the disciplinary character of students of Ibnul Qoyyim Putra Islamic Boarding School are the lack of communication with santri guardians, the lack of awareness of students regarding their purpose in the boarding school, and facilities and infrastructure in the form of fences that have not surrounded the Ibnul Qoyyim Putra Islamic Boarding School.